Do Clowns Really Taste Funny? An Investigation of the Relationship between Humor and Playfulness in Clown Doctors - Alberto Dionigi; Alessandra Fermani; Carla Canestrari (Behavioral Sciences, 2023)
Healthcare clowning represents a well-established method for relieving patients and their relatives of discomfort during hospitalization. Although studies concerning the effectiveness of this approach are increasing in number, state-of-the-art studies conducted to evaluate the psychological characteristics of clown doctors are scarce. In this cross-sectional study, a convenient sample of 210 clown doctors (143 females, 67 males) aged between 18 and 75 years (M = 47.34, SD = 12.31) completed a demographic questionnaire, the Comic Styles Markers, and the Short Measure for Adult Playfulness. The results demonstrated that clown doctors bring higher levels of fun, benevolent humor, and nonsense and a lower level of cynicism compared to the populace. Moreover, the participants with more experience tend to use less irony, sarcasm, and cynicism than those with less experience. Playfulness was primarily related to the lighter styles of humor, and specific differences between the Whiteface and the Auguste clown doctors were observed. The results are discussed with reference to previous studies conducted on groups of clown doctors.